Evaluation of four anaesthetics in freshwater baitfish (Cheirodon interruptus) (Ostariophysi: Characidae) - Urzúa Pizarro, Natalia (2022)
The aim of this study was to evaluate the response of eugenol, propofol, isoflurane and lidocaine on physiological and anaesthesiologic variables of Cheirodon interruptus, the most widely used baitfish in Argentina. Six groups were formed: 25 mg/l eugenol, 50 mg/l eugenol, 300 mg/l lidocaine, 0.2 mg/l isoflurane, 0.4 mg/l isoflurane, and 5 mg/l propofol. The tests are carried out with water at a temperature of 18.03±2.1 °C, pH 6.87±0.18, dissolved oxygen 6.73±0.05 mg l-1 and conductivity 3.74±0.04 μS cm-. The initial weight (1.6±0.4 g) and total length (5.1±0.4 cm) were statistically similar between groups. The results indicate that eugenol and isoflurane meet the requirements that a good anaesthetic for use in fish should meet. For propofol and lidocaine, it is considered necessary to review the dosage to adapt its use in C. interruptus due to the long recovery time. The fish treated with isoflurane (0.4 mg/l) and propofol had a significant decrease (p<0.001 and p<0.05, respectively) between baseline respiratory rate and during anesthesia. None of the drugs used caused fish deaths.